Examining the influence of gender and social support in online learning motivation - Mohamed , Rosmaliza; Rahmat , Noor Hanim; Wan Mohamed , Wan Nazihah (Journal of Islamic, Social, Economics and Development, 2024)
The shift to online learning in Malaysia's education system, prompted by the COVID-19 pandemic, necessitates an examination of student motivation towards online learning mode. Understanding what drives students to participate in online educational activities is crucial. This study seeks to explore the factors affecting students' motivation that relates to expectancy beliefs, task value, and social support by focusing on gender differences. It also assesses the relationship between social support and online learning motivation. A questionnaire based on Fowler's framework was administered to undergraduate students at a public university in Kelantan. Analysis using t-test was applied to 165 responses which revealed no significant gender influence on expectancy beliefs, task value, or social support concerning online learning motivation. However, a strong positive correlation was found between social support and online learning motivation. The findings suggest that while gender does not significantly impact motivation variables, it has implications for both practical and theoretical aspects of online learning motivation. Future research frameworks should incorporate these various dimensions to create effective motivational strategies tailored to both genders. By identifying and addressing the specific motivational factors relevant to each gender, educators can implement more equitable online learning experiences that cater to the diverse needs of their students. This approach can enhance engagement and success in online learning environments, ultimately benefiting individual learners and the educational system as a whole.